2015
DOI: 10.1016/j.egypro.2015.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Al2O3 Thin Films Prepared by Thermal ALD

Abstract: International audienceThermal Atomic Layer Deposition was used to deposit Al2O3 layers with thickness ranging from 2 to 100 nm for surface passivation of silicon solar cells. Various characterization techniques were used to evaluate the chemical, physical and optical properties of the layers and interfaces. Minority carrier lifetime around 2 ms was measured for an optimal thickness of 15 nm for as-deposited layers on high resistivity n-type silicon substrate. An annealing step at 400 degrees C increases lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 6 publications
2
25
1
1
Order By: Relevance
“…Temperature was varied between 350°C and 450°C and annealing time was varied between 5 min and 15 min. As reported previously, maximum τ eff values around 5.8 ms were measured after annealing at 400°C for 10 min [8]. From the maximum τ eff value of 5.8 ms, the surface recombination velocity was estimated to S around 2.4 cm/s.…”
Section: Effect Of Thermal Annealing On the Properties Of The Al 2 O mentioning
confidence: 68%
See 1 more Smart Citation
“…Temperature was varied between 350°C and 450°C and annealing time was varied between 5 min and 15 min. As reported previously, maximum τ eff values around 5.8 ms were measured after annealing at 400°C for 10 min [8]. From the maximum τ eff value of 5.8 ms, the surface recombination velocity was estimated to S around 2.4 cm/s.…”
Section: Effect Of Thermal Annealing On the Properties Of The Al 2 O mentioning
confidence: 68%
“…For the present study the number of cycles was varied between 20 and 1000, leading to film thicknesses between 2 and 100 nm. More precisely, we measured previously a growth per cycle (GPC) of 0.098 nm per cycle at 250°C on Si substrates [8]. After as-deposited characterizations, the samples were annealed in the ALD chamber in direct contact with the chuck.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Microstructure and XRD studies (not shown) do not show a signal of the shell crystallization. The amorphous lattice of the Al 2 O 3 -shell is a common characteristic of the ALD-process [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…In the frame of microtechnologies, aluminium oxide (Al2O3) has been investigated for several applications: as a "high-k" material for MOS gate oxide [1,2], as an ion-sensitive and passivation layer for FET-based microsensors [3,4], as a passivation layer for OLED and solar cell devices [5,6], as a luminescent material for dosimeters [7],... As a consequence, many processes based on physical and/or chemical deposition techniques were developed in order to integrate alumina thin films with optimized properties into the corresponding fabrication processes: electron beam evaporation [8,9], pulsed laser deposition [10], sputtering [11], chemical vapour deposition [12], metal-organic chemical vapour deposition [13], plasma-enhanced chemical vapour deposition [14],... Among them, atomic layer deposition (ALD) was thoroughly studied for the conformal deposition of Al2O3 thin films [15][16][17], emphasizing the use of tri-methyl-aluminium Al(CH3)3 (also called TMA) as an aluminium source and water (H2O) as an oxidant source [18][19][20][21][22][23][24][25]. Nevertheless, other sources such aluminium trichloride (AlCl3) as well as dioxygen (O2) and ozone (O3), were also developed in parallel using plasma-enhanced atomic layer deposition (PE-ALD) in order to reduce the impurity content in the grown Al2O3 film and improve their dielectric properties [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In the different studies related to the ALD process [18][19][20][21][22][23][24][25][26][27][28], the presence of a steep interface was systematically assumed between the Al2O3 films and the silicon substrate, which allows simplifying the determination of the ALD growth rate per cycle as well as defining different growth types: linear, substrate-enhanced and substrate-inhibited [29]. This "steep interface" assumption seems obvious when considering the atomic layer deposition principles.…”
Section: Introductionmentioning
confidence: 99%